Clinical Test of Herbal Product Formulation of Combination of Ageratum conyzoides, Mussaenda frondosa, Curcuma longa and Uncaria gambir as Postpartum Antibacterial - Hujjatusnaini, Noor; Purwanti, Devi Yuni; Nirmalasari, Ridha; Dwi Rini Kurnia Fitri; Astuti Muh Amin; Mila (JURNAL KEBIDANAN, 2025)
Indonesia is a maritime country with tropical forests that possess various natural resources utilized to fulfill needs in clothing, shelter, and medicine. Certain medicinal plants such as Ageratum conyzoides, Mussaenda frondosa, Curcuma longa, and Uncaria gambir have medicinal properties, including antibacterial effects for postpartum infections. The limited knowledge among the public regarding the benefits of traditional medicinal plants is due to restricted dissemination of information through digital media, among other factors.  Therefore, it is crucial that information about the clinical trials of herbal products containing a combination of Ageratum conyzoides, Mussaenda frondosa, Curcuma longa, and Uncaria gambir as postpartum antibacterials is conveyed to the younger generation, especially millennials, and those unfamiliar with the diversity of plants. A non-parametric research design method was employed, testing the pharmacological effects of the herbal product formulation through preliminary data. Data collection involved obtaining responses from 50 participants who used the herbal product, including 15 with vaginal discharge, 10 postpartum individuals, 10 with dysmenorrhea, 5 with postpartum infections, 5 unmarried healthy individuals, and 5 married healthy individuals, using the Wilcoxon test. The research results indicate that the combined herbal formulation significantly affected the test groups with indicators such as vaginal discharge, postpartum without infection, postpartum with infection, dysmenorrhea, and married and healthy individuals, with a significance level of 0.01. These results suggest positive potential. Further analysis reveals that the group without infection complaints did not show a significant impact. In conclusion, the combination formulation demonstrates positive effectiveness in groups with specific complaints related to infection and reproductive disorders. However, the response to the formulation may vary depending on initial health conditions and the characteristics of the target group.